PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI DAN PELATIHAN TERHADAP KINERJA KARYAWAN BAGIAN TEKNISI PADA PT. TELKOM WILAYAH DENPASAR CABANG RENON - I Wayan Yudi Wiratama; Made Ika Prastyadewi; I Nyoman Resa Adhika (VALUES, 2023)
Employee performance is an element used in evaluating employees of their work, position, and organization. performance is the result of a process that refers to and is measured over a certain period of time based on predetermined terms and agreements. This study aims to determine the effect of transformational leadership style, organizational culture and training on the performance of technician employees at PT. Telkom Region Denpasar Renon branch. Methods data collection was carried out by observing and using a questionnaire. The population of this study are employees of PT. Telkom Region Denpasar Renon branch. The sample in this study was 70 respondents with the type of Non Probability Sampling selected by Saturated Sampling (census). The data analysis technique used is multiple linear regression analysis using IBM SPSS 25 software. The instrument test results show valid and reliable data. The results showed that the transformational leadership style had a positive and significant effect on employee performance, organizational culture had a positive and significant effect on employee performance, training had a positive and significant effect on employee performance.